Determination of mass attenuation coefficient for some polymers using Monte Carlo simulation. (September 2015) - Singh, V.P.; Shirmardi, S.P.; Medhat, M.E.; Badiger, N.M.
Abstract: Mass attenuation coefficient, μ / ρ for some polymers with potential applications in dosimetry, and medical physics has been calculated using Monte Carlo simulation code, MCNP-4C at different gamma ray energies, 59.5, 279.1, 511, 661.6, 662, 1115.5, 1173, 1173.2, 1274.5 and 1332.5 keV. Appreciable variations were noted for mass attenuation coefficients for the polymers by changing the photon energy. The simulated μ / ρ values were compared with possible available experimental data and theoretical XCOM results, and good agreement was observed. Present study indicates that simulation geometry method is suitable to be used as an alternative method for the experiments. The present geometry can be used as standard geometry for MCNP simulation for low- Z materials. The calculated μ / ρ values using MCNP-4C code signify that the simulation geometry method can be followed to determine the gamma ray attenuation coefficients for the polymers for which there are no experimental values available. Highlights: μ / ρ values for polymers were calculated using MCNP. Good agreement among MCNP, XCOM and experiment was noted. Simulation geometry method is suitable as an alternate method for the experiments. MCNP simulation is appropriate to derive μ / ρ for dosimetric materials.